Accuracy of Visual Assessment of Urimeter Bag Volumes: The Whiz Quiz. Issue 11 (24th November 2022) - Margulies, Samantha L.; Osment, Anna E.; Schroeder, Michelle N.; Geller, Elizabeth J.
Abstract : Importance: Although visual estimate of urine output via urimeter bag is common, data on accuracy are limited. Objective: This study aimed to assess the accuracy of a visual estimate of urine output in standard urimeter bags by health care workers. Study Design: This is a prospective observational study. Perioperative health care workers were asked to visually estimate fluid volumes in 5 standard urimeter bags. Actual volumes were 50, 150, 350, 500, and 750 mL. Visual estimates were recorded. The primary outcome was accuracy, defined as estimated visual volume within 20% of actual volume. Secondary outcomes included effect of health care provider type, specialty, experience, sex, and age on accuracy. Results: A total of 159 responses were analyzed. There were 55 (35.3%) registered nurses, 19 (12.2%) certified registered nurse anesthetists, 18 (11.5%) advanced practice providers not identified as a certified registered nurse anesthetist, and 64 (41%) physicians. Mean estimated volumes (in milliliters) ± standard deviation and accuracy for the bags were as follows: (a) actual volume of 50 mL and estimated volume of 66 ± 29 mL (45% accuracy), (b) actual volume of 150 mL and estimated volume of 149 ± 43 mL (46% accuracy), (c) actual volume of 350 mL and estimated volume of 356 ± 74 mL (76% accuracy), (d) actual volume of 500 mL and estimated volume of 452 ± 77 mL (85% accuracy), and (e) actual volume of 750 mL and estimated volume of 675 ± 108 mL (85% accuracy). There was reasonable accuracy for individual volume estimates, but accuracy across all 5 urimeter bags was low: 22 of 159 (13.8%). There were no significant differences in accuracy based on health care provider type, specialty, experience, sex, or age. Conclusions: Consistent accuracy of visual assessment of calibrated urimeter bag volumes was low and not influenced by health care provider characteristics.